A Extrema Esquerda brasileira e a Revolução Cubana (1959-1974) - Ferreira, André Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
O advento da Revolução Cubana em 1959 representou um ponto de inflexão na trajetória dos movimentos sociopolíticos da América Latina no século XX. Inspiradas pela vitória dos rebeldes em Cuba, várias organizações de extrema esquerda do continente aderiram à luta armada e à teoria do foco guerrilheiro nos anos 60 e 70. No Brasil, após o Golpe de Estado de 1964, diferentes grupos promoveriam ações revolucionárias contra a ditadura militar instaurada. As idéias de Che Guevara, Fidel Castro e Régis Debray desencadeariam intermináveis debates político-ideológicos entre as diversas correntes de orientação marxista. No presente trabalho procuramos avaliar como a experiência da Revolução Cubana foi apropriada pelas organizações clandestinas brasileiras e, da mesma forma, como seu exemplo serviu para legitimar determinadas posições de setores do movimento comunista no país.

The Cuban Revolution advent in 1959 represented a point of inflection in the trajectory of sociopolitical movements in Latin America in the century XX. Inspired for the rebel's victory in Cuba, several extreme left wing organizations of the continent adhered to the armed combat and the theory of guerrilla focus in the 60's and 70's. In Brazil after the coup d'etat in 1964, different groups would promote revolutionary actions against the established military dictatorship. Che Guevara's, Fidel Castro's and Régis Debray's ideas would trigger endless political-ideological arguments among several groups of Marxist orientation. In the present work we try to evaluate how the experience of the Cuban Revolution was appropriate to the Brazilian clandestine organizations and, in the same way, how their example served to legitimate certain positions of the communist movement in the country.
The Extreme Brazilian Left and the Cuban Revolution (1959-1974)
Keywords: Comunismo; Guerrilhas - Guerra e operações; Brasil Historia 1964-1985; Cuba História Revolução 1959; Cuban Revolution; Communism; Armed combat; Military dictatorship; Guerrilla war